x(x)-12x=-8

Simple and best practice solution for x(x)-12x=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x)-12x=-8 equation:


Simplifying
x(x) + -12x = -8

Multiply x * x
x2 + -12x = -8

Reorder the terms:
-12x + x2 = -8

Solving
-12x + x2 = -8

Solving for variable 'x'.

Reorder the terms:
8 + -12x + x2 = -8 + 8

Combine like terms: -8 + 8 = 0
8 + -12x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-8' to each side of the equation.
8 + -12x + -8 + x2 = 0 + -8

Reorder the terms:
8 + -8 + -12x + x2 = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -12x + x2 = 0 + -8
-12x + x2 = 0 + -8

Combine like terms: 0 + -8 = -8
-12x + x2 = -8

The x term is -12x.  Take half its coefficient (-6).
Square it (36) and add it to both sides.

Add '36' to each side of the equation.
-12x + 36 + x2 = -8 + 36

Reorder the terms:
36 + -12x + x2 = -8 + 36

Combine like terms: -8 + 36 = 28
36 + -12x + x2 = 28

Factor a perfect square on the left side:
(x + -6)(x + -6) = 28

Calculate the square root of the right side: 5.291502622

Break this problem into two subproblems by setting 
(x + -6) equal to 5.291502622 and -5.291502622.

Subproblem 1

x + -6 = 5.291502622 Simplifying x + -6 = 5.291502622 Reorder the terms: -6 + x = 5.291502622 Solving -6 + x = 5.291502622 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 5.291502622 + 6 Combine like terms: -6 + 6 = 0 0 + x = 5.291502622 + 6 x = 5.291502622 + 6 Combine like terms: 5.291502622 + 6 = 11.291502622 x = 11.291502622 Simplifying x = 11.291502622

Subproblem 2

x + -6 = -5.291502622 Simplifying x + -6 = -5.291502622 Reorder the terms: -6 + x = -5.291502622 Solving -6 + x = -5.291502622 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = -5.291502622 + 6 Combine like terms: -6 + 6 = 0 0 + x = -5.291502622 + 6 x = -5.291502622 + 6 Combine like terms: -5.291502622 + 6 = 0.708497378 x = 0.708497378 Simplifying x = 0.708497378

Solution

The solution to the problem is based on the solutions from the subproblems. x = {11.291502622, 0.708497378}

See similar equations:

| 4m+7(3m-8)= | | (2+x)(x)(3)=240 | | -.3p-2.1=-3.6 | | 3x(x)+14x-5=0 | | (4200*2/3)6 | | -2x+7(0)=11 | | 2x+4=2x+3(-1x+2) | | 25x=5x-20 | | 2(n-2)=4n+6 | | 2x+3-20=500 | | 1.5x(6-4)= | | 3a=7c | | 2x+4=2x+3(-x+2) | | 500=100+3n | | 24n+72=288 | | log[2](3x+2)=log[3](12x+3) | | x(x)+7x-5=0 | | f(x)=2x^2+7x-1 | | s^2-13st-30t^2=0 | | 1.5x(6-4)=3 | | -7c-8(9-6c)= | | x(x)+16x+39=0 | | 5+2y=7 | | 6y-13=55 | | 8(y+9)=7y-3 | | solven+(n+1)+(n+2)=54 | | 25-n/2=10 | | 3(-1)-2(1/2) | | .2(-10x+25)=3x(-3-4) | | x^3+17x^2+41x+3=0 | | 25x-28=3x-10 | | x(x)+17x+60=0 |

Equations solver categories